Kajian Yuridis Gelit Jeneng Adat Kejawen dalam Penetapan Wali Adhal - Putri Diana Lestari; Wiwin Yulianingsih (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2022)
Currently, there are many requests for guardian judges for the continuation of a marriage. One of them is the reason that the lineage guardian does not want to be a guardian. This refusal is accompanied by the reason that there is a gelit jeneng in kejawen custom. This study aims to identify and analyze the kejawen traditional jeneng in determining the guardian adhal, namely regarding the arrangements to the position of the guardian adhal. This research is a normative juridical law research using qualitative analysis method, which produces analytical descriptive data, by obtaining data through literature study and interviews. Sources of data obtained from literature, scientific papers and applicable laws and regulations. The results of the study can be concluded that the guardian adhal has been regulated in positive law. The wali adhal arrangement in positive law only states that the guardian judge can act to replace the adhal guardian nasab if there has been a determination from the Religious Court. Further provisions regarding consideration of the reasons for the guardian's application are not regulated in Indonesian positive law. At a certain point, there was an application for a wali adhal because it was a bitch, the stipulation of a wali adhal was based on the pillars and legal requirements, as well as the prohibition on marriage contained in positive Indonesian law. Thus, tickling jeneng is ruled out in the determination of the adhal guardian because it is considered not to be included in the prohibition of marriage. With the issuance of the determination of the guardian adhal by the Religious Court, the position of the guardian of the lineage can be replaced by the guardian of the judge.